Experience with infections in the use of extracorporeal membrane oxygenation - Rosa María Calderón Checa; Pablo Rojo Conejo; Aranzazu Flavia González-Posada Flores; Ana María Llorente de la Fuente; Alba Palacios Cuesta; Juan Miguel Aguilar; Sylvia Belda Hofheinz (Elsevier, 2018)
Objective: To identify risk factors associated with infectious complications acquired by paediatric patients during extracorporeal life support (ECLS). Patients and methods: Patients under ECLS from January 2011 to December 2014 have been retrospectively reviewed and data on demographics, care and infectious complications were collected. Results: There were 50 ECLS assistances in the study period, of which 20 patients had 23 infectious complications: 16 were bloodstream infections, with coagulase negative staphylococci being the predominant isolate (there were 2 cases of candidaemia). Age, site of cannulation procedure, cannulation site, severe coagulopathy, and surgical interventions during assistance were analysed as risk factors for infectious complications, but no significant differences were found. ECLS duration was significantly longer in patients with infectious complications (8.91 vs 5.91 days; P = .039). There were no significant differences as regards Paediatric Intensive Care Unit (PICU) stay, or in survival. Conclusions: Infectious complications during ECLS are very common, and ECLS duration is significantly longer in patients with infections. Measures should be put in place to prevent infectious complications and reduce time on ECLS. Resumen: Objetivo: Identificar factores de riesgo asociados con el desarrollo de infecciones nosocomiales en pacientes pediátricos asistidos con oxigenación por membrana extracorpórea (ECMO). Pacientes y métodos: Se han revisado de forma retrospectiva los pacientes que han recibido asistencia en ECMO de enero de 2011 a diciembre de 2014. Se han recogido datos demográficos, sobre la asistencia y sobre las infecciones que aparecen durante dicha asistencia. Resultados: En este periodo hubo 50 asistencias en ECMO. Veinte pacientes tuvieron 23 episodios de infección, de los que 16 fueron bacteriemias, siendo el microorganismo más frecuente el estafilococo coagulasa negativo (habiendo 2 casos de candidemia). En cuanto a los grupos de edad, el lugar y el tipo de canulación, la presencia de coagulopatía grave y la realización de intervenciones quirúrgicas durante la asistencia, ninguno de estos factores resultó un factor de riesgo de infección estadísticamente significativo. La duración media de soporte en ECMO fue significativamente mayor en los pacientes que tuvieron alguna infección (8,91 vs. 5,96 días; p = 0,039). No hubo diferencias significativas en cuanto a la estancia en la Unidad de Cuidados Intensivos Pediátricos ni en cuanto a la supervivencia. Conclusiones: La incidencia de infección durante ECMO es muy alta y los pacientes que tienen una infección están asistidos un tiempo significativamente mayor, por lo que se deben instaurar medidas para prevenir la aparición de estas infecciones e intentar minimizar el tiempo de asistencia en ECMO.